Helicobacter pylori Activates HMGB1 Expression and Recruits RAGE into Lipid Rafts to Promote Inflammation in Gastric Epithelial Cells - Lin, Hwai-Jeng; Hsu, Fang-Yu; Chen, Wei-Wei; Lee, Che-Hsin; Lin, Ying-Ju; Chen, Yi-Ywan M.; Chen, Chih-Jung; Huang, Mei-Zi; Kao, Min-Chuan; Chen, Yu-An; Lai, Hsin-Chih; Lai, Chih-Ho (Frontiers in Immunology, 2016)
Helicobacter pylori infection is associated with several gastrointestinal disorders in the human population worldwide. High-mobility group box 1 (HMGB1), a ubiquitous nuclear protein, mediates a variety of inflammation functions. The interaction between HMGB1 and receptor for advanced glycation end-products (RAGE) triggers nuclear factor (NF)-κB expression, which in turn stimulates the release of proinflammatory cytokines such as interleukin (IL)-8 and enhances the inflammatory response. However, how H. pylori activates HMGB1 expression and mobilizes RAGE into cholesterol-rich microdomains in gastric epithelial cells to promote inflammation has not been explored. In this study, we found that HMGB1 and RAGE expression increased significantly in H. pylori-infected cells compared to uninfected cells. Blocking HMGB1 by neutralizing antibody abrogated H. pylori-elicited RAGE, suggesting that RAGE expression follows HMGB1 production, and silenced RAGE-attenuated H. pylori-mediated NF-κB activation and IL-8 production. Furthermore, significantly more RAGE was present in detergent-resistant membranes extracted from H. pylori-infected cells than in those from uninfected cells, indicating that H. pylori exploited cholesterol to induce the HMGB1 signaling pathway. These results indicate that HMGB1 plays a crucial role in H. pylori-induced inflammation in gastric epithelial cells, which may be valuable in developing treatments for H. pylori-associated diseases.